An investigation into the hydrodynamics of a flexible riser undergoing vortex-induced vibration. (May 2016) - Song, Leijian; Fu, Shixiao; Cao, Jing; Ma, Leixin; Wu, Jianqiao
Abstract: In this study, a method to obtain the hydrodynamic forces of a flexible riser undergoing vortex-induced vibration (VIV) based on measured strain is proposed. The tensioned riser is approximated as an Euler–Bernoulli beam, and an inverse method is adopted for the calculation of the hydrodynamic forces in the cross flow (CF) and inline (IL) directions. Based on these hydrodynamic forces, and combined with the VIV velocities and accelerations of the riser, the excitation and added-mass coefficients are obtained through a least-squares method. As an illustration example, the hydrodynamic characteristics of a flexible riser model undergoing VIV in a uniform flow are investigated. Results indicate that VIV leads to non-uniform distribution of the drag coefficient and amplifies the drag coefficient along the riser. Similar distribution of the energy transfer coefficient has been found between the entire riser and that of the CF direction. For synchronized VIV occurring in both CF and IL directions, the energy transferred from the fluid is all dissipated by the structural damping, and hence leads to the energy balance in both CF and IL directions. It further shows that the excitation coefficients on flexible riser undergoing VIV do not agree with those of the forced oscillation tests: excitation coefficients sometimes even become negative within the normally excitation regime, and are related with not only the non-dimensional frequency and amplitude but also the phase angles between the CF and IL vibrations. The added-mass coefficient of flexible risers does not keep a constant value of 1.0 anymore, but depends on the non-dimensional frequency and amplitude of vibration. Highlights: A method for obtaining hydrodynamics of a flexible riser under VIV is proposed. VIV leads to non-uniform distribution of drag forces and amplifies drag forces. For synchronized VIV, the energy is balance along both CF and IL directions. The excitation coefficients of flexible riser and rigid cylinder are different. The added-mass coefficients of flexible riser do not have a constant value of 1.0.